1999
DOI: 10.1902/jop.1999.70.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Fibromatosis Combined With Cherubism and Psychomotor Retardation: A Rare Syndrome

Abstract: Gingival fibromatosis is frequently an isolated condition, but rarely associated with some uncommon syndromes. This paper describes an 11-year-old patient with pronounced gingival enlargement, cherubic facial appearance, and psychomotor retardation and discusses the major aspects of the case. The most striking finding orally was the presence of grossly hyperplastic gingiva, which completely covered all teeth except the occlusal surfaces of some teeth. The swelling in the lower part of the face and the appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
1
11
0
4
Order By: Relevance
“…In the present case, features such as epilepsy, GF, mental retardation in the setting OMIM online mendelian inheritance in man of cherubism may well relate to Ramon syndrome though hypertrichosis was not a feature [8][9][10]. Review of literature revealed that cherubism have been reported in association with gingival fibromatosis [5], psychomotor retardation and gingival fibromatosis [24], neurofibromatosis and multiple non-ossifying fibromas of the femoral bone [25,26], and Fragile X syndrome [27]. Others have reported diabetes mellitus, vascular skin lesions and ocular abnormalities as part of Ramon syndrome [12,21,22].…”
Section: Discussionmentioning
confidence: 55%
“…In the present case, features such as epilepsy, GF, mental retardation in the setting OMIM online mendelian inheritance in man of cherubism may well relate to Ramon syndrome though hypertrichosis was not a feature [8][9][10]. Review of literature revealed that cherubism have been reported in association with gingival fibromatosis [5], psychomotor retardation and gingival fibromatosis [24], neurofibromatosis and multiple non-ossifying fibromas of the femoral bone [25,26], and Fragile X syndrome [27]. Others have reported diabetes mellitus, vascular skin lesions and ocular abnormalities as part of Ramon syndrome [12,21,22].…”
Section: Discussionmentioning
confidence: 55%
“…1,4,19,20 Bu ol gu çalış-masında, ai le sel ge çi şi gös te ren soy ağa cı in ce lendi ğin de, ay nı an ne den do ğan üç ço cuk ta da HGF gö rül me si ve ba ba la rın da bu lun ma ma sı, bu has ta lı -ğın oto zo mal do mi nant ge çiş li ol du ğu nu des tek lemek te dir.…”
Section: Tar Tiş Maunclassified
“…HGF'nin men tal re tar das yon, epi lep si, hi per tri koz, Zim mermann-La band, Ra mon, Cross sen dro mu gi bi durum lar la bir lik te gö rü le bil di ği bil di ril miş tir. 1,3,7,19 Fa kat bu ol gu çalışmasında in ce le nen hiç bir ai le bire yin de her han gi bir ek bul gu ya rast lan ma dı. Tüm ai le bi rey le ri men tal açı dan nor mal ve sis te mik olarak sağ lık lı idi.…”
Section: Tar Tiş Maunclassified
See 2 more Smart Citations